Fabrication and electrical characterization of flower-like CdO/p-Si heterojunction diode - Caglar, M.; Yakuphanoğlu, Fahrettin (Iop Publishing Ltd, 2009)
The electrical properties of a flower-like CdO/p-Si heterojunction diode have been investigated in the temperature range 80-400 K. The CdO thin film was deposited on p-type Si using the sol-gel spin coating method. The scanning electron microscope result indicates that the film has a flower-like structure. From the x-ray diffraction result, it is shown that the CdO film has a polycrystalline structure with preferential orientation along the (1 1 1) crystal plane. The optical band gap of the CdO film was found to be 2.57 eV. The ideality factor is n >> 2 which is due to the presence of non-ideal contact behaviour and the result of inhomogeneity and tunnelling. At lower temperatures, the charge transport mechanism results from the tunnelling mechanism, whereas at higher temperatures, it is controlled by recombination currents. The capacitance-voltage characteristic shows a typical abrupt heterojunction.
Keywords: Thin-Films; Optical-Properties; Oxide-Films